Intelligent metro optical networks and key optical components - Li XIAO; Zhilin YUAN; Chengpeng FU; Weidong MA (Dianxin kexue)
Driven by the background of escalating internet traffic,the requirements of intellectualization and flexibility on metro optical transportation networks were dramatically increasing,which promoted network architecture revolution.ROADM network element and its dynamic networking technology which played the core role in intelligent all-optical metro networks were introduced.Metro network was cost sensitive,thus low-cost key optical components as the keys for physical realization of ROADM network element were studied,as well as decoupled white box optical components and their programmability.It was concluded that the low cost white box ROADM network elements were the key and effective means for optical metro networks intelligentialization.